Fostering Respectful and Productive Conversations: Lessons Learned From Debating Courtyards in Tibetan Buddhist Monasteries - Sangpo, Lodoe; Dhuldhoya, Manan; Dhuldhoya, Niyati; Dias, Brian G (Frontiers in Communication, 2021)
A suspicion for perspectives that differ from one’s own is not new to human interactions. What is new, however, is the disregard and the resultant disrespect that colours mainstream discourse across the globe today, whether in the media or in person. This creates barriers to healthy interaction and hence to learning from collaboration. Our team comprises a Tibetan Buddhist monk, a writer, an editor, and a neuroscientist, and we hope this paper, guided and crafted by a regard for the diversity of our experiences across two continents, can demonstrate how respectful and productive conversations can be achieved. We begin by stating the need for forms of communication that are very different from prevailing modes of interaction. We then examine the mechanics of debate that form the foundations of communication and learning in Buddhist monastic communities and discuss how this form of debate can help us arrive at harmonious interactions. Finally, we propose a format for respectfully initiating, maintaining, and ending conversations that take place anywhere from the classroom to the boardroom and newsroom.